Developing a Project-Based Learning Course Model Combined with the Think-Pair-Share Strategy to Enhance Creative Thinking Skills in Education Students - Meng-Meng Li; Chia-Ching Tu (MDPI AG, 2024)
The aim of this research was to produce a project-based learning (PjBL) course model that combines with the Think-Pair-Share (TPS) strategy and to determine its effectiveness in improving the creative thinking skills of education students. The sample of participants comprised 100 students from a university in Bangkok, Thailand. Five main elements comprised the PjBL-TPS course: 1. Project Preparation (including an introduction, pairs formation, and an understanding of the project); 2. Project Pair Cooperation (including discussion, knowledge framework development in pairs, practice analysis, brainstorming, and pair feedback); 3. Project Production (including its development, testing, refinement, and presentation); 4. Project Evaluation (including giving feedback on the work of the other pairs); and 5. Project Conclusion (including reflecting on the overall experience of the project). The results show that, in their post-course exercises, the students displayed enhanced creativity in all areas of creative skills (involving fluency, flexibility, originality, and elaboration). The experimental group demonstrated significantly higher creativity levels compared to the control group. In addition, the post-course assessments of the self-perceived creativity improvements of the students revealed that, post-course, most of the students perceived improvements in every aspect of their creativity.